The relationship of achievement and sociometric status to classroom behavior of grade two students - Keough, Lorraine Elizabeth, 1956- (1980)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1980. Education Bibliography: leaves 52-57. The purpose of this study was to investigate the relationship of academic achievement and sociometric status to classroom behaviors of grade two pupils. -- Nine classrooms from schools in rural St. John's participated in the study, with four learning problem and four average achievers serving as target students in each classroom. Determination of achievement group resulted from teacher rankings on reading achievements. Sociometric status was assessed on two dimensions using the Ohio Social Acceptance Scale: social attraction - mean score given to all other classmates by a student; and social acceptance - mean score recieved from all other classmates by one pupil. -- All target students were observed for thirty second intervals on a rotating basis using the Classroom Motivation Observation Scale. -- Comparison of behaviors observed by achievement and sociometric status, using 2 and 3-way ANOVAS showed significant behavior differences for each of the variables observed in the study. Eight distinct student types emerged as a result of the combination of achievement, social acceptance, and social attraction group. These were: High attraction - low acceptance - average achievers, good quiet students who drew little teacher attention;- learning problem, who were typical trouble makers disrupting peers and teacher. High attraction - high acceptance - average achievers, popular students who worked with peers but used the teacher to maintain peer approval;- high attraction, high acceptance learning problem, quiet slow students, who although spending a lot of time non-attending, were non-disruptive. Low attraction - low acceptance - average achievers, good students who worked well alone and with the 'teacher, but did not interact with peers. Low attraction, low acceptance, learning problem, active attention seekers who get the attention of the teacher by disruptive behaviors. Low attraction - high acceptance, average achievers, ideal students with high on-task teacher contacts and lower than average disruptive behaviors. Low attraction, high, acceptance, learning problem, who disrupted peers in an effort to gain teacher attention. -- The results of this study have several implications for classroom teaching. Different patterns of interactions were found for different teachers suggesting different amounts of tolerance for types of classroom behaviors exhibited by students. Finding supported recent research indicating average achieving students exhibited higher amounts of on-task behavior. Differences in peer directed behavior exhibited by the eight types of students in this study could serve as a means for teachers to understand peer relations in the classroom and help control disruptive behavior.